Comparison between a multicentre, collaborative, closed-loop audit assessing management of supracondylar fractures and the British Orthopaedic Association Standard for Trauma 11 (BOAST 11) guidelines. (March 2018) - Goodall, R.; Claireaux, H.; Hill, J.; Wilson, E.; Monsell, F.; BOAST 11 Collaborative,; Tarassoli, P.
Abstract : Aims: Supracondylar fractures are the most frequently occurring paediatric fractures about the elbow and may be associated with a neurovascular injury. The British Orthopaedic Association Standards for Trauma 11 (BOAST 11) guidelines describe best practice for supracondylar fracture management. This study aimed to assess whether emergency departments in the United Kingdom adhere to BOAST 11 standard 1: a documented assessment, performed on presentation, must include the status of the radial pulse, digital capillary refill time, and the individual function of the radial, median (including the anterior interosseous), and ulnar nerves. Materials and Methods: Stage 1: We conducted a multicentre, retrospective audit of adherence to BOAST 11 standard 1. Data were collected from eight hospitals in the United Kingdom. A total of 433 children with Gartland type 2 or 3 supracondylar fractures were eligible for inclusion. A centrally created data collection sheet was used to guide objective analysis of whether BOAST 11 standard 1 was adhered to. Stage 2: We created a quality improvement proforma for use in emergency departments. This was piloted in one of the hospitals used in the primary audit and was re-audited using equivalent methodology. In all, 102 patients presenting between January 2016 and July 2017 were eligible for inclusion in the re-audit. Results: Stage 1: Of 433 patient notes audited, adherence to BOAST 11 standard 1 was between 201 (46%) and 232 (54%) for the motor and sensory function of the individual nerves specified, 318 (73%) for radial pulse, and 247 (57%) for digital capillary refill time. Stage 2: Of 102 patient notes audited, adherence to BOAST 11 standard 1 improved to between 72 (71%) and 80 (78%) for motor and sensory function of the nerves, to 84 (82%) for radial pulse, and to 82 (80%) for digital capillary refill time. Of the 102 case notes reviewed in stage 2, only 44 (43%) used the quality improvement proforma; when the proforma was used, adherence improved to between 40 (91%) and 43 (98%) throughout. Conclusion: Adherence to BOAST 11 standard 1 is poor in hospitals across the country. This is concerning as neurovascular deficit may be an indication for emergent surgery, and missed neurovascular injury can cause long-term, or even permanent, functional impairment. We present a simple proforma that improves adherence to this standard, can easily be implemented into emergency departments, and may improve patient safety. Cite this article: Bone Joint J 2018;100-B:346–51.